(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Context: Non-communicable diseases (NCDs) are the leading cause of morbidity and mortality worldwide, with India contributing a significant share of the global burden. The early onset and poor control of NCDs in rural populations highlight the need for comprehensive risk factor assessment. Aims & Objectives: This study aimed to determine the prevalence of behavioural, physical, and biochemical risk factors among adults with NCDs and find out their association with metabolic control. Materials & Methods: A cross-sectional analytical study was conducted from September 2023 to February 2024 at a tertiary care hospital in Theni, Tamil Nadu. Using systematic random sampling, 402 adults (≥18 years) attending the NCD outpatient clinic were enrolled. Data were collected employing the WHO STEPS approach, encompassing behavioural, physical, and biochemical parameters. Statistical analyses were performed using Epi-Info; categorical variables were tested using the Chi-square test, and P<0.05 was considered statistically significant. Results: Among the 402 participants, 55.2% had uncontrolled blood pressure (BP), 51% exhibited poor glycaemic control (fasting blood glucose ≥126 mg/dL), and 31.6% had elevated total cholesterol (≥190 mg/dL). Low physical activity (72.1%), obesity (36.8%), tobacco (16.9%), and alcohol use (15.4%) were found among the study participants. Smoking and alcohol use were significantly associated with poor glycaemic control (P=0.001, P=0.021), while alcohol consumption was linked to uncontrolled Blood Pressure (P=0.031). None of the variables were found to be associated with elevated Total Cholesterol. Conclusion: A high prevalence of modifiable risk factors and poor metabolic control underscores the urgent need for integrated lifestyle interventions and robust primary healthcare strategies to mitigate the escalating NCD burden in rural India.